Automated analysis of a large-scale paediatric dataset illustrates the interdependent relationship between epilepsy and sleep - Jelena Skorucak; Bigna K. Bölsterli; Sarah Storz; Sven Leach; Bernhard Schmitt; Georgia Ramantani; Reto Huber (Scientific Reports, 2023)
Abstract Slow waves are an electrophysiological characteristic of non-rapid eye movement sleep and a marker of the restorative function of sleep. In certain pathological conditions, such as different types of epilepsy, slow-wave sleep is affected by epileptiform discharges forming so-called “spike-waves”. Previous evidence shows that the overnight change in slope of slow waves during sleep is impaired under these conditions. However, these past studies were performed in a small number of patients, considering only short segments of the recording night. Here, we screened a clinical data set of 39′179 pediatric EEG recordings acquired in the past 25 years (1994–2019) at the University Children’s Hospital Zurich and identified 413 recordings of interest. We applied an automated approach based on machine learning to investigate the relationship between sleep and epileptic spikes in this large-scale data set. Our findings show that the overnight change in the slope of slow waves was correlated with the spike-wave index, indicating that the impairment of the net reduction in synaptic strength during sleep is spike dependent.